2001
DOI: 10.1017/s0959270901000211
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of Blue and Gold Macaw Ara ararauna into its historical range on Trinidad

Abstract: New World parrots are declining throughout their range. Blue and Gold Macaw Ara ararauna was extirpated from the island of Trinidad in the late 1960s through anthropogenic processes. The Cincinnati Zoo & Botanical Garden is assisting the Wildlife Section of the Forestry Division, Trinidad on a mission to restore the species into its historical range within the Bush-Bush Sanctuary in the Nariva Swamp. The Sanctuary has been protected by the government of Trinidad and is the home of the endangered Red-bellied Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…The extensive consumption of palm fruits, mainly during the dry season, was also noted elsewhere at preserved areas (Roth, 1984;Sick, 1997;Oehler et al, 2001). These nutritive and, potentially, abundant fruits were available when fleshy fruits often decline in tropical areas (van Schaik et al, 1993).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The extensive consumption of palm fruits, mainly during the dry season, was also noted elsewhere at preserved areas (Roth, 1984;Sick, 1997;Oehler et al, 2001). These nutritive and, potentially, abundant fruits were available when fleshy fruits often decline in tropical areas (van Schaik et al, 1993).…”
Section: Discussionmentioning
confidence: 87%
“…In fact, the importance of these fruits is particularly pronounced in marked seasonal areas where asynchronous fruits tend to exhibit no redundancy with seasonal fruits (Peres, 2000;Ragusa-Netto, 2010), potentially, the case at the studied urban area. Recently, the reduction of palm density in natural areas has been assumed as the cause of macaw influx to palm orchards (Oehler et al, 2001). In principle, this may be the case in the urban area of Três Lagoas where palms are common due to their ornamental importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These D. P. Tubelis studies identified many other food items. My study in grassland and woodland firebreaks adds six species to the known diet of plant species eaten by the Blue-and-yellow Macaw in the Cerrado and in general (Haverschmidt, 1954;Roth, 1984;Forshaw, 1989;del Hoyo et al, 1997;Sick, 1997;Juniper and Parr, 1998;Oehler et al, 2001;Trivedi et al, 2004;Haugaasen and Peres, 2005;Sigrist, 2006). As sampling occurred between September and February, further studies, especially in other periods of the year, might identify other plant species that are consumed by macaws in the region of Emas National Park.…”
Section: Feeding Ecology Of Ara Ararauna At Firebreaksmentioning
confidence: 99%
“…Seed consumption has been observed in countries such as Surinam, Peru and Brazil (Haverschmidt, 1954;Trivedi et al, 2004;Haugaasen and Peres, 2005). Equally frequent are reports of fruit consumption, especially palm fruits (Roth, 1984;Sick, 1997;Oehler et al, 2001). Also, there are brief comments on A. ararauna eating fruits of other plants (Roth, 1984;Sick, 1997;Sigrist, 2006).…”
Section: Introductionmentioning
confidence: 99%